2005
DOI: 10.1111/j.1443-9573.2005.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Common single nucleotide polymorphism of hypoxia‐inducible factor‐1α and its impact on the clinicopathological features of esophageal squamous cell carcinoma

Abstract: Although there is no significant difference of genotype distribution between ESCC patients and healthy controls, genotype C/T is associated with larger tumor and higher rate of lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 15 publications
4
29
1
Order By: Relevance
“…In this study, the C1772T and G1790A mutation rates in pancreatic cancer were 10% (1/10) and 0%, respectively, for pancreatic cancer and 6.3% (1/16) and 6.3% (1/16), respectively, for gallbladder cancer (all heteromutation-type). These results, together with those of previous reports (2,(8)(9)(10)(11) show a low SNP rate for all cancers, except renal cancer, suggesting the lack of an association between SNPs and carcinogenesis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, the C1772T and G1790A mutation rates in pancreatic cancer were 10% (1/10) and 0%, respectively, for pancreatic cancer and 6.3% (1/16) and 6.3% (1/16), respectively, for gallbladder cancer (all heteromutation-type). These results, together with those of previous reports (2,(8)(9)(10)(11) show a low SNP rate for all cancers, except renal cancer, suggesting the lack of an association between SNPs and carcinogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…However, type 2 diabetes mellitus is a risk factor for pancreatic cancer, which suggests an association between the development of pancreatic cancer and the SNPs of HIF-1α. There have been studies on an association between carcinogenesis and HIF-1α SNPs in cancer in various organs (2,(8)(9)(10)(11). The C1772T and G1790A mutation rates were reported to be 18 and 11%, respectively, in patients with head or neck cancer, and 11 and 8%, respectively, in healthy subjects, with no statistically significant differences between the 2 groups (2).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the distribution of C1772T genotypes in control groups was approximately similar to those reported in previous studies (Clifford et al, 2001;Tanimoto et al, 2003;Ling et al, 2005). We found no evidence of a relationship between clinicopathological characteristics and C1772T polymorphism in endometrial cancer patients.…”
Section: 10393 the Polymorphism Of Hypoxia-inducible Factor-1a Gene supporting
confidence: 72%
“…In accordance with the inclusion criteria, 8 case-control studies (Kuwai et al, 2004;Ling et al, 2005;Fransen et al, 2006;Li et al, 2009;Hsiao et al, 2010;Knechtel et al, 2010;Kang et al, 2011;Wang et al, 2011) were included in this meta-analysis and 91 articles were excluded. The flow chart of the study selection process is shown in Figure 1.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…However, the exact mechanism of these polymorphisms in the development of digestive cancer is not clearly understood (Huang et al, 2012). Recent evidence has suggested that HIF-1α gene polymorphisms may be associated with increased digestive cancer risk (Ling et al, 2005;Fransen et al, 2006;Li et al, 2009;Hsiao et al, 2010;Kang et al, 2011;Wang et al, 2011); however, individually published results are inconclusive (Kuwai et al, 2004;Knechtel et al, 2010). Therefore, we attempt to perform a meta-analysis of all eligible case-control studies to provide insights into these associations, which may promote our understanding of the exact role of the HIF-1α gene in the development of carcinogenesis in the digestive organs.…”
Section: Introductionmentioning
confidence: 99%